Buried in the archives: cemeteries and mausolea in Tripolitania. (November 2019) - Ray, Nick; Nikolaus, Julia
Abstract: Much extant research on monumental burial structures considers mausolea in isolation from one another, both spatially and temporally, separating them from the more extensive cemeteries that either pre-existed or were built up around them. This paper presents the preliminary results of an ongoing archive-based project studying Tripolitanian Roman-period funerary landscapes, specifically investigating the relations between mausolea and their adjacent cemeteries. These relations start to help us understand the patterns in the burial traditions of the region and demonstrate the importance of the ongoing interaction between the living and the monuments of the dead. Furthermore, this study demonstrates the importance of archival research, especially in areas that are inaccessible due to conflict. Abstract : دُفِنَ في الأرشيف : المقابر و الأضرحة في إقليم تريبوليتانيا (طرابلس ) بقلم نيك راي وجوليا نيكولاس توجد الكثير من الأبحاث عن مباني الدفن الأثرية حيث تنظرهذه الابحاث في الأضرحة بمعزل عن بعضها البعض، من الناحيتين المكانية والزمانية، و بذلك تقوم هذه الأبحاث بفصلها عن المقابر الأكثر شمولاً التي كانت موجودة مسبقاً أو بنيت من بعد من حولها . تعرض هذه الورقة النتائج الأولية لمشروع قائم و مستمر - يستند على الأرشيف - يقوم بدراسة المشهد الجنائزي لإقليم تريبوليتانيا (طرابلس ) و الذي يرجع إلى الحقبة الرومانية، ويبحث بشكل خاص في العلاقات بين الأضرحة والمقابر المجاورة لها. هذه العلاقات تساعدنا في بدء فهم أنماط تقاليد الدفن في المنطقة وإظهار أهمية التفاعل المستمر بين الأحياء وأثار الأموات . علاوة على ذلك، توضح هذه الدراسة أهمية البحوث الأرشيفية، لا سيما في المناطق التي يتعذر الوصول إليها بسبب الصراع .